Chronic organophosphate-induced neuropsychiatric disorder: a case report - Ghimire SR; Parajuli S (Neuropsychiatric Disease and Treatment)
Shree Ram Ghimire,1 Sarita Parajuli2 1Department of Psychiatry, National Medical College, Birgunj, 2Department of Anesthesiology, Kathmandu National Medical College, Anamnagar, Kathmandu, Nepal Abstract: Chronic organophosphate (OP)-induced neuropsychiatric disorder is a rare condition following prolonged exposure to OP compounds. Due to the lack of valid diagnostic tools and criteria, very few cases are seen in clinical practice and are often misdiagnosed. Misdiagnosis can lead to inappropriate treatment that may increase the risk of morbidity or suicidality. In this paper, we present the case of a 35-year-old male who needed support in breathing from a mechanical ventilator and developed neuropsychiatric behavioral problems following ingestion of OP compounds, which lead to suicidality. The patient was treated by the psychiatric team with antipsychotic and antidepressants and improved following the regular use of medication. Keywords: COPIND, mood liability, suicidal thoughts